The Tradition Of Dau Balak in Lampung Traditional Marriage ‘Urf Perspective - Miftahudin Azmi; Arini Shohiha al-Haq (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
Indonesia has a very diverse marriage tradition, one of which is the marriage fee (Dau Balak) which must be given to the prospective husband to the prospective wife's family in the Lampung traditional marriage system. The marriage is canceled if there is no nominal agreement between the dau balak, whereas previously for several days. Moreover, Dau Balak's funds are not part of the marriage dowry. This study aims to analyze the requirements of Dau Balak in Lampung traditional marriages from the perspective of 'urf. This research is included in the type of empirical research (field research) using a qualitative descriptive approach. The results showed that the deliberation process in determining the number of Dau Balak was based on the spirit of kinship, if the prospective husband's family had not been able to accept the number of Dau Balak, it could be continued with a proposal (nyukak) to the prospective wife. Then the husband was given the opportunity for some time to pay Dau Balak, if he could not pay then the proposal was cancelled. The values ​​and goals of Dau Balak are proof of the seriousness of the prospective husband in navigating domestic life. Therefore, Dau Balak is included in the category of 'urf sahih, because in the process there are no practices that are contrary to Islamic law. The Dau Balak fund in the Lampung traditional Sebambangan marriage system includes authentic evidence that can be accepted by 'urf